Up-regulation of iNOS by hypoxic postconditioning inhibits H9c2 cardiomyocyte apoptosis induced by hypoxia/re-oxygenation. (3rd June 2015) - Zhao, Huanxin; Yang, Rong; Shi, Yujuan; Yang, Wanfang; Zeng, Qun; Zhao, Guoyi; Wang, Xiaoliang
Abstract: Apoptosis is a crucial mode of cell death induced by ischemia and reperfusion, and ischemic postconditioning (PostC) has been reported to inhibit cell apoptosis. Inducible nitric oxide synthase (iNOS) has been confirmed to play an important role in triggering and mediating the late cardio-protection against ischemia/hypoxia. In this study, we found that hypoxic PostC remarkably up-regulated the expression of iNOS and decreased cardiomyocyte apoptosis. Pre-treatment with 1400w (a highly selective inhibitor of iNOS) or iNOS siRNA weakened the anti-apoptotic effect of hypoxic PostC. These findings suggested that iNOS may be one of the key molecular mechanisms responsible for the inhibition of apoptosis by hypoxic PostC.